A novel scheme for simulating the force-free equations : boundary conditions and the evolution of solutions towards stationarity - Carrasco, Federico León; Reula, Oscar Alejandro (2024)
Artículo finalmente publicado en: Carrasco, F. L. y Reula, O. A. (2017). A novel scheme for simulating the force-free equations: boundary conditions and the evolution of solutions towards stationarity. Physical Review D, 96 (6), 063006. https://doi.org/10.1103/PhysRevD.96.063006